齿根裂纹与轮齿啮合刚度关联规律研究 - 唐进元; 王志伟; 伊洪丽; 陈思雨 (Jixie chuandong)
Gear mesh stiffness is the foundation of the study on gear dynamics.Taking the spur gear as research object,the finite element model of the spur gear with root crack is established,and the accurate calculation method of gear mesh stiffness is proposed based on the finite element quasi-static analysis principle.Through analysis,the influence rule of crack parameter on gear time-varying meshing stiffness is obtained,the result of numerical calculation shows that,the value of mesh stiffness reduces obviously when the crack appears,the crack parameters（the crack length and the crack direction） have a significant effect on gear mesh stiffness,and the crack length plays an important role,the reduce of gear stiffness depends on the meshing position of gear,the value of stiffness reduces quickly when the gear meshing position is at the highest point of single tooth meshing.